Celiac Disease - Reinaldo Alexander; Murdani Abdullah (The Indonesian Society for Digestive Endoscopy, 2017)
Celiac disease is a multisystem autoimmune disorder, which is induced by dietary gluten exposure. This disease usually found in European population, but with the increase of Asian population tendency to eat western style, which contain gluten, celiac disease frequency is expected to increase in Asian population for the near future. The finding of diagnostic modalities which is highly sensitive and specific, starting with the antigliadin, and then the antiendomysium and anti-transglutaminase antibodies, has increased the awareness of clinicians and patients towards this condition. The understanding of definition, pathogenesis, diagnostic procedure, and current management of celiac disease is needed to avoid morbidity and mortality of this disease.